Proximal Stimulus for Brewster's Phenomenon is Equivalent to That of Wheatstone's Stereogram. (May 2017) - Ono, Hiroshi; Lillakas, Linda
We examined Brewster's perceptual phenomenon that is produced by the same binocularly equivalent proximal stimulus as Wheatstone's stereogram. We then constructed and observed the perceptual effect created by another distal stimulus that also created an equivalent binocular proximal stimulus. All three stimulus situations produced the appearance of a tilted line in the median plane which is consistent with Hering's rule that the average of the two local signs and binocular eye position determine visual direction. The characteristics of the proximal stimulus are also relevant to the question raised by Helmholtz regarding the empirical vertical horopter.